(untitled) (Nigerian Journal of Pharmaceutical Research, 2021)
Background: The emergence of multidrug-resistance Enterobacteriaceae especially in E. coli bacteria associated with Urinary Tract Infections (UTIs) in pregnancy is a serious menace globally posing health challenges and confounding successful empirical treatment as well as increasing pregnancy-related complications. Objectives: The aim of this study is to determine the phenotypic and genotypic characteristics of Extended Spectrum Beta – Lactamases (ESBLs) producing E. coli (ESBLs – EC) isolates in pregnant women attending ante–natal clinics within Ilorin - Kwara State, Nigeria. Materials and methods: A total of 53 non - repeated E. coli isolates from urine samples of pregnant women were presumptively identified using standard bacteriological method and confirmed by commercially available Microgen® Identification Kits. Phenotypic detection of ESBLs was determined using antibiotics susceptibility test and double disc synergy Method for screening and confirmation respectively. Polymerase Chain Reaction (PCR) was further used for the genotypic detection of ESBLs genes. Results: A total 88.67% (47/53) of E. coli exhibited resistance to the cephalosporins of which aztreonam was the highest (75.47%) and the least was cefpodoxime (35.84%) while 85.10% were confirmed positive for ESBL production. The genotypic detection showed the most occurring genotype was blaTEM (50%) blaOXA (27.7%), blaGES (22.5%), blaSHV (15%), blaCTXM and blaVEB (7.5%) while sixty – four (64%) of isolates co – harbored two or more gene. BlaTEM and blaOXA were dominant. Conclusion: This study showed high resistance of E. coli to the third generation cephalosporins harboring different ESBL genes which increases UTIs complexity and limit therapeutic options in pregnancy. Therefore, continuous monitoring of resistance in E. coli, effective appraisal of antibiotic control policies and rational use of antibiotics is therefore encouraged.